Naagan ge bezhig emkwaan: A Dish with One Spoon Reconsidered - Jacobs, Dean; Lytwyn, Victor (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
Bkejwanong—the place where the waters divide (the delta islands of Lake St. Clair)—has been called the “soul” of Anishinaabe territory. Long before Europeans arrived, the Anishinaabe occupied territory which includes parts of present-day Ontario, Michigan and Ohio. The resources found there are integral to their way of life and identity. The Anishinaabe defended this territory against Haudenosaunee warriors in the seenteenth century and its integrity was at the core of the peace they concluded in Montreal in 1701, a key element of which was the Naagan ge bezhig emkwaan, or Dish with One Spoon. The dish represented the territory and the single spoon symbolized that people from other territories would be able to eat together while peace was maintained. Recently, however, the Dish with One Spoon has been popularized as an agreement to protect the environment. The original treaty has been incorporated into “land recognition statements” that blur the territorial rights of individual First Nations. This transformation is damaging to First Nations who seek to protect their territories and resources. Walpole Island First Nation (the Council of Three Fires) is working to reclaim their Dish.